Analyzing students’ misconceptions about newton’s lws through four-tier newtonian test (FTNT) - Kanıawatı, Ida; Fratıwı, Nuzulira Janeusse; Danawan, Agus; Suyana, Iyon; Samsudın, Achmad; Suhendı, Endi (Journal of Turkish Science Education, 2024)
This research aimed at analyzing student misconceptions about Newton’s Laws through Four-Tier Newtonian Test (FTNT). The research involved 30 students (15 boys and 15 girls, whose ages were middling of 16 years-old) at one of Senior High School in Bandung, Indonesia. The data were analyzed through mixed methods. Based on the quantitative analysis, the highest percentage of student misconceptions through four-tier test was 66% and through two-tier test was 100%. According to qualitative analysis, it was found student misconceptions about Newton’s Laws. From the research, it can be concluded that FTNT can be used in analyzing student misconceptions on Newton’s Laws concepts and more effective than using the two-tier test. Teachers or researchers can expand the concepts of Newton’s Laws that are used in designing diagnostic test and developed for other physics concepts.